Evaluation of bond strength between grooved titanium alloy implant abutments and provisional veneering materials after surface treatment of the abutments: An in vitro study - Gowtham Venkat; Murugesan Krishnan; Suganya Srinivasan; Muthukumar Balasubramanian (Wolters Kluwer Medknow Publications, 2017)
Introduction: Titanium has become the material of choice with greater applications in dental implants. The success of the dental implant does not only depend on the integration of the implant to the bone but also on the function and longevity of the superstructure. The clinical condition that demands long-term interim prosthesis is challenging owing to the decreased bond between the abutment and the veneering material. Hence, various surface treatments are done on the abutments to increase the bond strength. Aim: This study aimed to evaluate the bond strength between the abutment and the provisional veneering materials by surface treatments such as acid etching, laser etching, and sand blasting of the abutment. Materials and Methods: Forty titanium alloy abutments of 3 mm diameter and 11 mm height were grouped into four groups with ten samples. Groups A, B, C, and D are untreated abutments, sand blasted with 110 μm aluminum particles, etched with 1% hydrofluoric acid and 30% nitric acid, and laser etched with Nd: YAG laser, respectively. Provisional crowns were fabricated with bis-acrylic resin and cemented with noneugenol temporary luting cement. The shear bond strength was measured in universal testing machine using modified Shell-Nielsen shear test after the cemented samples were stored in water at 25°C for 24 h. Load was applied at a constant cross head speed of 5 mm/min until a sudden decrease in resistance indicative of bond failure was observed. The corresponding force values were recorded, and statistical analysis was done using one-way ANOVA and Newman-Keuls post hoc test. Results: The laser-etched samples showed higher bond strength. Conclusion: Among the three surface treatments, laser etching showed the highest bond strength between titanium alloy implant abutment and provisional restorations. The sand-blasted surfaces demonstrated a significant difference in bond strength compared to laser-etched surfaces. The results of this study confirmed that a combination of surface treatments and bond agents enhances the bond strength.